Inhaled cyanide poisoning as a vital sign in a room fire victim. (December 2017) - Birngruber, Christoph G.; Veit, Florian; Lang, Juliane; Verhoff, Marcel A.
Highlights: The case of a victim of a room fire is presented. Autopsy and histological examinations did not reveal any vital signs. COHb level was 3%, inhaled cyanide intoxication was the only vital sign. Toxicological examinations are indispensable in fire victims. Abstract: The corpse of a 71-year-old woman was found on the floor of her smoke-filled room. The source of the fire was the mattress of a double bed on which newspapers had apparently been set aflame. The woman's history in conjunction with the finding situation suggested an act of suicide. No signs of soot inhalation or soot swallowing were found at autopsy. Other vital signs were absent. Severe cardiac disease was the most notable pre-existing medical condition. Although the concentration of COHb in heart blood was low (3%), the concentration of cyanide was found to be 4.3 mg/l in heart blood and 1.9 mg/l in lung tissue. Cyanide was not found in the stomach contents. The BAC (blood alcohol concentration) was zero. Several prescribed drugs could also be demonstrated. The cause of death was deemed to be cyanide poisoning, possibly in conjunction with the pre-existing cardiac disease. The reported case illustrates that a lethal amount of cyanide can be inhaled during a fire even if there is no inhalation or swallowing of soot and no significant increase in the COHb level. In such cases, the demonstration of cyanide assumes significance as a vital sign indicating that the victim was alive when the fire started.